I. Treatment of Ulcerative Colitis - Yoshida, Y. (Nippon Daicho Komonbyo Gakkai Zasshi, 1978)
Physicians are reminded the following three facts on treating the patients with ulcerative colitis ; 1) The disorder is a chronic inflammation and the affected colon is much irritated. 2) Immunological process is playing a role in the pathogenesis. 3) Approximately 20% of the patients will be ultimately treated surgically. General measures of treatment are the colonic, physical and emotional rest, maintenance of nutrition and of fluid and electrolytes balance, and other managements for improvement of general status. As chemotherapeutic measures, in patients with mild or moderate colitis Salazopyrine is the drag of first choice and steroid enema is the second. Oral administration of steroid is given to patient with refractory and severe colitis. In acute fulminant colitis no oral intake is allowed, and all medications and nutritions are given parenterally. If no definite improvement is seen within a week surgical treatment is urgent. Indication of surgical treatment for ulcerative colitis is not definite, but the cases which do not respond to medical treatment for some weeks are generally indicated. Since the prognosis for patients with severe colitis on medical management is not good, earlier surgery has been recommended. For maintenance of remission, administration of Salazopyrine may be used for more than 6 months.